MINAT SISWA TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMP NEGERI 30 MUARO JAMBI - Wawan Junresti Daya; Deka Ismi Mori Saputra (Jurnal Muara Olahraga, 2020)
Based on the results of observations at 30 Muaro Jambi Public Middle School, the learning process of Physical Education, Sports and Health at the school was not as expected. It was still apparent that some students who still often came late to the field hindering physical education learning, some even sometimes don't bring sports clothes. And his lack of interest is evidenced by the fact that some of the students are still often seen chatting and playing with their own friends when the teacher is explaining the material outside or inside the room, so that students do not know or do not understand the explanation given by the teacher, and some students look ashamed to ask which parts are not clear and don't understand.The purpose of this study was to determine student interest in participating in physical education and sports education. This research was conducted on February 15, 2020 until April 9, 2020. This type of research is a quantitative descriptive study using survey methods and data collection techniques using tests and measurements, so that it provides an overview of what will be examined in the form of numbers and measured with certainty. Based on various considerations as stated above, those who will be used as informants (research subjects) are grade VII students at SMP Negeri 30 Muaro Jambi, totaling 135 studentsThe calculation results above can be concluded that the students' interest in learning Physical and Sports Physical Education in Muaro Jambi State Junior High School 30 is included in both categories with a percentage of 77% which is in the interval between 61-80%. The conclusion in this study is the interest of students in learning Physical Education and Sports in 30 Muaro Jambi State Junior High Schools included in both categories with a percentage of 77%.